2007
DOI: 10.1111/j.1365-2249.2007.03368.x
|View full text |Cite
|
Sign up to set email alerts
|

Potato lectin activates basophils and mast cells of atopic subjects by its interaction with core chitobiose of cell-bound non-specific immunoglobulin E

Abstract: SummaryA major factor in non-allergic food hypersensitivity could be the interaction of dietary lectins with mast cells and basophils. Because immunoglobulin E (IgE) contains 10-12% carbohydrates, lectins can activate and degranulate these cells by cross-linking the glycans of cell-bound IgE. The present objective focuses on the effect of potato lectin (Solanum tuberosum agglutinin; STA) for its ability to release histamine from basophils in vitro and mast cells in vivo from non-atopic and atopic subjects. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…Dietary lectins have been shown to release histamine from mast cells and basophils as a result of their interaction with cell-surface IgE molecules resulting in activation [42]. Earlier, it has been demonstrated from this laboratory that horse gram lectin (specificity for GalNAc) does not induce HR from leukocytes whereas potato lectin (specificity for core GlcNAc-GlcNAc) induces HR from leukocytes of atopic subjects [27,28]. Since core GlcNAc-GlcNAc and trimannosidic core are present in almost all of the glycans of N-linked glycoproteins including IgE, our results indicate the propensity of garlic lectins to non-specifically activate mast cells and basophils in atopics as a result of higher density of IgE.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Dietary lectins have been shown to release histamine from mast cells and basophils as a result of their interaction with cell-surface IgE molecules resulting in activation [42]. Earlier, it has been demonstrated from this laboratory that horse gram lectin (specificity for GalNAc) does not induce HR from leukocytes whereas potato lectin (specificity for core GlcNAc-GlcNAc) induces HR from leukocytes of atopic subjects [27,28]. Since core GlcNAc-GlcNAc and trimannosidic core are present in almost all of the glycans of N-linked glycoproteins including IgE, our results indicate the propensity of garlic lectins to non-specifically activate mast cells and basophils in atopics as a result of higher density of IgE.…”
Section: Discussionmentioning
confidence: 95%
“…Atopic and non-atopic subjects were identified based on case history (atopic subjects chosen at random who had clinical symptoms of at least one allergic condition among the following: allergic rhinitis, asthma, and food allergy) of the subjects and SPT results with commercial extracts of house dust mite, and pollens [27,28]. The following allergenic extracts were used for SPT for confirming the allergic status: grass pollen mix 1, grass pollen mix 2, house dust mite and weed pollen mix.…”
Section: Spt Of Atopic and Non-atopic Subjectsmentioning
confidence: 99%
“…108 Of potential relevance to food allergy, several authors have reported that plant lectins may act as superallergens by binding IgE glycans and inducing cross-linking. 109,110 In addition, Lavelle et al 111 have reported that a number of plant lectins have mucosal adjuvant activity when administered orally. Finkelman 112 has reported that an undefined low-molecular-weight constituent of peanut extract can directly induce an anaphylactoid response in a complement-dependent manner, although whether this biological activity may also be important for innate immune activation and contribute to T H 2 polarization has not been reported.…”
Section: Direct Effector Cell Activation (Superallergens)mentioning
confidence: 98%
“…Hemagglutination assay was performed according to the procedure of Burger (1974) using rabbit or human erythrocytes as described earlier (Pramod and Venkatesh, 2006;Pramod et al, 2007). Guduchi stem extract was prepared as described in Section 2.3; sample containing 20 mg protein in 3 mL was loaded on a column of Sephadex G-50 (1.8 cm × 157 cm) pre-equilibrated with phosphate-buffered saline (PBS), and elution was carried out using PBS at a flow rate of 12.5 mL/h.…”
Section: Plant Materials Collection and Extractionmentioning
confidence: 99%